Expediente e apresentação da edição - v. 15, n. 3 - Nozu, Washington Cesar Shoiti; Siebiger, Ralf Hermes (Eventos Pedagógicos, 2024)
Expediente e apresentação da edição - 40 ed., v. 15, n. 3, ago./dez. 2024.